Knowledge, Attitude, and Behavior of Depok Residents regarding Child Sexual Abuse - Sari, Fitri Ambar (Jurnal Forensik dan Medikolegal Indonesia, 2019)
Depok City, West Java, demographically located adjacent to capital city of Indonesia. This geographic condition makes Depok city experience high pressure of population migration as the result of increasing number in residential area, higher education level, expanding commerce and service and also from rapid growth of population in every sub-district. One of the negative impact from this condition is Depok City ranked fourth highest in number of offences against children, right after Jakarta, Tangerang, and Bekasi. Therefore; Depok is currently in the “red zone” or in the other words, child abuse emergency. Data from Pusat Pelayanan Terpadu Pemberdayaan Perempuan dan Anak (P2TP2A) Depok till August 2017, there were 167 cases of child and woman abuse from which 75 cases’ victim are children. Moreover, in period of January to June 2018, the number of child and woman abuse has reached 60 cases, and from those 60 cases, there were 40 cases of sexual abuse. The aforementioned situation encouraged Team from Forensic Medicine and Medicolegal, Faculty of Medicine University of Indonesia to do campaign against sexual abuse in children at one of sub-district in Depok City. In this campaign, team also conducted a survey to determine the level of knowledge, attitudes, and behavior of Depok residents regarding child sexual abuse. The survey was conducted in July 2018 using 71 respondents consisted of parents and adolescents.